Is the alcohol industry doing well by "doing good"? Findings from a content analysis of the alcohol industry's actions to reduce harmful drinking - Babor, Thomas F. (2018)
Objectives The aims of this study were to: (1) describe alcohol industry corporate social responsibility (CSR) actions conducted across six global geographic regions; (2) identify the benefits accruing to the industry ('doing well'); and (3) estimate the public health impact of the actions ('doing good'). Setting Actions from six global geographic regions. Participants A web-based compendium of 3551 industry actions, representing the efforts of the alcohol industry to reduce harmful alcohol use, was issued in 2012. The compendium consisted of short descriptions of each action, plus other information about the sponsorship, content and evaluation of the activities. Public health professionals (n=19) rated a sample (n=1046) of the actions using a reliable content rating procedure. Outcome measures WHO Global strategy target area, estimated population reach, risk of harm, advertising potential, policy impact potential and other aspects of the activity. Results The industry actions were conducted disproportionately in regions with high-income countries (Europe and North America), with lower proportions in Latin America, Africa and Asia. Only 27% conformed to recommended WHO target areas for global action to reduce the harmful use of alcohol. The overwhelming majority (96.8%) of industry actions lacked scientific support (p<0.01) and 11.0% had the potential for doing harm. The benefits accruing to the industry ('doing well') included brand marketing and the use of CSR to manage risk and achieve strategic goals. Conclusion Alcohol industry CSR activities are unlikely to reduce harmful alcohol use but they do provide commercial strategic advantage while at the same time appearing to have a public health purpose.